Gestão da inovação aberta: modelo de acesso à inovação tecnológica - Lopes, Eloisa de Moura (2011)
The management of technological innovation is a major challenge for managers nowadays. Understand the significance of independent variables that sustain the process to access the technological innovation, allow the managers to translate the technological profile of their companies and contribute to their business decision related to the desired innovation. The objective of this study is the model to access technological innovation. In order to analyze the significance of independent variables, it was used inferential statistics analyses by Design of Experiments in two steps: first, Plackett-Burman method was applied with a matrix N=8, and then Experimental 2(k-p) design was applied with 95% confidence interval. The statistic calculation was done using independent variables, and these variables were selected based on the correlation to dependent variables through F test. Nevertheless, two of the independent variables (competitive intelligence and open innovation) were selected based on the Thesis project content. One of the hypotheses of this project determines that the variables, competitive intelligence (CI) and open innovation (OI) are significant in the process to access technological innovation. Seventy innovative Brazilian companies were selected as the population of this study, where information was provided by business managers in innovation area. Main results demonstrate that nine variables are independently significant for the studied model, such as: support to new ideas, systematic research for new products ideas, OI, measuring of innovation, CI, high management commitment, partnerships with Universities, time control and project budget and sharing innovation with everyone in the company. Besides it, thirteen interaction among the variables are significant, such as: support to new ideas and OI, support to new ideas and time control and project budget, OI and encouraging experimentation, encouraging experimentation and CI, systematic research for new products ideas and CI, stimulus to new ideas and high management involvement, methods to understand clients needs and communication of innovation strategy, communication of innovation strategy and CI, relationship among departments and CI, methods to understand clients needs and OI, effective structure to making decisions and IC, propagation of knowledge inside the company and CI, and OI and CI. We conclude that to access technological innovation, the variables, CI and OI are essential elements.